1990
DOI: 10.1017/s0021859600075262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary copper sulphate on the performance of growing Japanese quail

Abstract: SUMMARYThe effect of 200, 400 and 600 mg dietary copper sulphate/kg was studied in 64 Japanese quail (Coturnix coturnix japonica) in 1987. The results indicated that addition of 200 or 400 mg/kg to conventional diets of quail 7–42 days old significantly increased (P < 0·05) body weight gain and significantly decreased (P < 0·05) feed intake. There were significant (P < 0·05) increases in carcass, breast and leg weights in some cases; the first two characters had the highest values in the quail fed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In another experiment with Japanese quail slaughtered at 8 weeks of age, liver percentage was 2.06% in males and 3.52% in females (Aydin and Cook, 2004). Yannakopoulos et al (1990) found that liver percentage in 42-day-old Japanese quail was 3.50%. At the age of 45 days, Pharaoh quail had a lower percentage of gizzard than 35-dayold birds (Table 7).…”
Section: Resultsmentioning
confidence: 94%
“…In another experiment with Japanese quail slaughtered at 8 weeks of age, liver percentage was 2.06% in males and 3.52% in females (Aydin and Cook, 2004). Yannakopoulos et al (1990) found that liver percentage in 42-day-old Japanese quail was 3.50%. At the age of 45 days, Pharaoh quail had a lower percentage of gizzard than 35-dayold birds (Table 7).…”
Section: Resultsmentioning
confidence: 94%